Experiential manufacturing: designing meaningful relationships between people, data and things - Selby, Mark (2017)
This thesis presents a practice-led research investigation into ways of designing more experiential and evocative interactions with data that relates to our experiences whereby less explicit, more intrinsic and aesthetic relationships are made between people, objects and data. I argue that the utilitarian values and instrumental approach behind the design of most systems that mediate our personal autobiographical data, while important, are not appropriate for more emotional forms of remembering. Therefore, systems are needed that cater specifically to modes of remembering such as reminiscence and reflection. By learning from our material encounters with memory, there are rich opportunities for design to uncover the latent values that might exist in biographical data. To articulate the design rationale of the thesis, I describe two existing design projects: the Digital Slide Viewer and Photobox. These provide some design principles that offer guidance in making memory data physical so as to encourage meaningful material practices, and ways that interactions might be designed to promote reflection. After exploratory interviews to gather insight into the ways people associate meaning with objects a set of designed provocations were produced. The Poker Chip sought to understand the ways that the material form of an object connects to its meaning, while The Bowl investigates how the actions we might use to make these meaningful objects might in themselves be meaningful. The final designed provocation takes ideas from its predecessors, and puts them into practice with a data driven system. By responding to live data from real earthquakes, the Earthquake Shelf creates a tangible rendition that, by damaging objects, leaves behind material evidence of a remote event. During a long-term field deployment, connection between the objects on the shelf and the participant’s memories proved illusive, but the shelf itself provided a viscerally real connection to a past experience. The outcome of this thesis then is to articulate Experiential Manufacturing; a position on the design of technologies intended to mediate more emotional forms of memory, such that they can create more compelling relations between data, people, and things. It does this by first opening and exploring a design space based on alternative values for designing technologies of reminiscence that mediate our life experiences. By prioritizing the aesthetic elements of the experiences, rather than focusing on the data that describes it, this thesis explores the potential of material, liveness and slowness to create systems that mediate our experience data in more evocative and emotionally valuable ways. It then presents this position as a set of thematic values, or Strong Concepts at the heart of Experiential Manufacturing.